Gigantomastia and Macroprolactinemia Responding to Cabergoline Treatment: A Case Report and Minireview of the Literature - Fatma Dilek Dellal; Didem Ozdemir; Cevdet Aydin; Gulfem Kaya; Reyhan Ersoy; Bekir Cakir (Case Reports in Endocrinology)
Background. Macroprolactinemia is defined as predominance of high molecular weight prolactin forms in the circulation. Although macroprolactin is considered as a biologically inactive molecule, some authorities suggest treatment in symptomatic cases. Gigantomastia is defined as excess breast tissue and most cases in the literature were treated by surgical intervention. Case. A 44-year-old woman was admitted to our clinic with gigantomastia and galactorrhea. The patient had a demand for surgical therapy. In laboratory examination, she had hyperprolactinemia and macroprolactinemia. Pituitary imaging revealed 6 mm microadenoma in right side of the hypophysis. Since she was symptomatic, cabergolin treatment was started. Macroprolactin became negative, breast circumference decreased significantly, and galactorrhea resolved after treatment. Conclusion. Gigantomastia might be the presenting symptom in patients with macroprolactinemia. In these patients medical treatment with cabergoline may be used initially as an alternative to surgical approach.